2016
DOI: 10.1016/j.colsurfa.2015.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis and scanning curves in linear arrays of mesopores with two cavities and three necks

Abstract: Adsorption of argon at 87K in a linear array of slit mesopores composed of two cavities and three necks has been investigated using Grand Canonical Monte Carlo simulation. Hysteresis and scanning was found to depend on the relative size of the necks and cavities and on whether the necks are wider or narrower than the critical width that demarcates cavitation from pore blocking. There are 26 possible combinations for the linear array. By considering the behaviour of hysteresis scanning curves, we are able to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In the literature, there were a number of computer simulation studies (molecular dynamics or Monte Carlo) reported where SCPM chains with finite lengths (typically up to L = 5) were considered. They revealed that their phase-transition behavior depends strongly on the order of the pore sections with different pore sizes. This means that, for chains with large L , the number of different realizations can quickly approach values that are beyond the computational capabilities.…”
Section: Statistical Theory For the Phase State In A Serially Connect...mentioning
confidence: 99%
“…In the literature, there were a number of computer simulation studies (molecular dynamics or Monte Carlo) reported where SCPM chains with finite lengths (typically up to L = 5) were considered. They revealed that their phase-transition behavior depends strongly on the order of the pore sections with different pore sizes. This means that, for chains with large L , the number of different realizations can quickly approach values that are beyond the computational capabilities.…”
Section: Statistical Theory For the Phase State In A Serially Connect...mentioning
confidence: 99%
“…Do, Nicholson, and co-workers have demonstrated, in a series of publications using grand canonical Monte Carlo (GCMC) simulations with Lennard-Jones (LJ) fluids, that the isotherm of pore structures consisting of just a few serially connected pores of simple geometry (slits or cylinders) can be reconstructed as a linear combination of the local isotherms of appropriately chosen independent unit cells. In performing such a reconstruction, one must be provided with kernels of sorption isotherms on three different types of pores based on their condensation–evaporation mechanism: (i) pores with both ends open where capillary condensation during adsorption is delayed with respect to pressure due to metastability, (ii) pores with both ends closed where evaporation during desorption is due to cavitation, and (iii) pores with one end open and one closed, where condensation or evaporation occurs under equilibrium. Accordingly, proper knowledge of the exact location of each pore in the structure leads to the correct reconstruction of both adsorption and desorption isotherms in these small structures.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate their technical potential, hierarchical MFI‐type zeolite has been prepared in a large‐scale via desilication process, shaped into extrudates using various binders, [ 333 ] characterized by various physico‐chemical techniques, and successfully tested as catalysts for methanol to hydrocarbon (MTH) reaction. [ 334 ] Besides, significant success has been demonstrated in the synthesis of mesostructured zeolite Y via surfactant‐templating process in an industrial scale and tested as a FCC catalyst in a refinery, exhibiting excellent hydrothermal stability and catalytic cracking selectivity. [ 167 ]…”
Section: Application Opportunitiesmentioning
confidence: 99%